Clinical impact of a gastrointestinal PCR panel in children with infectious diarrhoea. Issue 6 (17th December 2021) - Truong, Jeanne; Cointe, Aurélie; Le Roux, Enora; Bidet, Philippe; Michel, Morgane; Boize, Julien; Mariani-Kurkdjian, Patricia; Caseris, Marion; Hobson, Claire Amaris; Desmarest, Marie; Titomanlio, Luigi; Faye, Albert; et al.
Abstract : Objectives: Multiplex gastrointestinal PCR (GI-PCR) allows fast and simultaneous detection of 22 enteric pathogens (including Campylobacter, Salmonella, Shigella /enteroinvasive Escherichia coli (EIEC), among other bacteria, parasites and viruses). However, its impact on the management of children with infectious diarrhoea remains unknown. Patients/Design: All children eligible for stool culture from May to October 2018 were prospectively included in a monocentric study at Robert-Debré University-Hospital. Intervention: A GI-PCR (BioFire FilmArray) was performed on each stool sample. Main measures: Data on the children's healthcare management before and after GI-PCR results were collected. Stool culture results were also reported. Results: 172 children were included. The main criteria for performing stool analysis were mucous/bloody diarrhoea and/or traveller's diarrhoea (n=130). GI-PCR's were positive for 120 patients (70%). The main pathogens were enteroaggregative E. coli (n=39; 23%), enteropathogenic E. coli (n=34; 20%), Shigella /EIEC (n=27; 16%) and Campylobacter (n=21; 12%). Compared with stool cultures, GI-PCR enabled the detection of 21 vs 19 Campylobacter, 12 vs 10 Salmonella, 27 Shigella/ EIEC vs 13 Shigella, 2 vs 2 Yersinia enterocolitica, 1 vs 1 Plesiomonas shigelloides, respectively. Considering the GI-PCR results and before stool culture results, the medical management was revised for 40 patients (23%): 28 initiations, 2 changes and 1 discontinuation of antibiotics, 1 hospitalisation, 2 specific room isolations related to Clostridioides difficile infections, 4 additional test prescriptions and 2 test cancellations. Conclusion: The GI-PCR's results impacted the medical management of gastroenteritis for almostone-fourth of the children, and especially the prescription of appropriate antibiotic treatment before stool culture results. Abstract : A prospective study of rapid PCR testing for stool pathogens in children with diarrhoea. Results were generally available two days more quickly than standard culture. This allowed more rational decisions about use of antibiotics in quarter of cases.